Diagonal Earlobe Crease is a Visible Sign for Cerebral Small Vessel Disease and Amyloid-β. Issue 1 (December 2017) - Lee, Jin; Park, Seongbeom; Kim, Hee; Kim, Yeshin; Jang, Hyemin; Kim, Ko; Rhee, Hak; Yoon, Sung; Hwang, Kyoung; Park, Key-Chung; Moon, Seung; Kim, Sung; et al.
Abstract We investigated the frequency and clinical significance of diagonal earlobe crease (DELC) in cognitively impaired patients using imaging biomarkers, such as white matter hyperintensities (WMH) on MRI and amyloid-β (Aβ) PET. A total of 471 cognitively impaired patients and 243 cognitively normal (CN) individuals were included in this study. Compared with CN individuals, cognitively impaired patients had a greater frequency of DELC (OR 1.6, 95% CI 1.1–2.2, P = 0.007). This relationship was more prominent in patients with dementia (OR 1.8, 95% CI 1.2–2.7, P = 0.002) and subcortical vascular cognitive impairment (OR 2.4, 95% CI 1.6–3.6, P < 0.001). Compared with Aβ-negative cognitively impaired patients with minimal WMH, Aβ-positive patients with moderate to severe WMH were significantly more likely to exhibit DELC (OR 7.3, 95% CI 3.4–16.0, P < 0.001). We suggest that DELC can serve as a useful supportive sign, not only for the presence of cognitive impairment, but also for cerebral small vessel disease (CSVD) and Aβ-positivity. The relationship between DELC and Aβ-positivity might be explained by the causative role of CSVD in Aβ accumulation.